Trade and Industrial Location with Heterogeneous Labor. (IMF Working Papers; Working Paper ;, 2004)
We show in the context of a new economic geography model that when labor is heterogenous trade liberalization may lead to industrial agglomeration and interregional trade. Labor heterogeneity gives local monopoly power to firms but also introduces variations in the quality of the job match. Matches are likely to be better when there are more firms and workers in the local market, giving rise to an agglomeration force that can offset the forces against trade costs and the erosion of monopoly power. We derive analytically a robust agglomeration equilibrium and illustrate its properties with numerical simulations.